An application of nonlinear integro-differential equations by differential transform method with Adomian polynomials. (1st January 2023) - Bao, Xuchao; Chan, Yue
In this paper, we introduce the modified differential transform method (MDTM), where the nonlinear terms in nonlinear integro-differential equations are replaced by Adomian polynomials so as to make the differential transform method (DTM) more efficient to compute. We provide a simple numerical example to illustrate its application. The modified method is also used to solve a nonlinear dynamic system problem of spherical robots.